2002
DOI: 10.1007/s00484-002-0134-2
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of large-scale and local climates on the demography of white-tailed ptarmigan in Rocky Mountain National Park, Colorado, USA

Abstract: Global climate change may impact wildlife populations by affecting local weather patterns, which, in turn, can impact a variety of ecological processes. However, it is not clear that local variations in ecological processes can be explained by large-scale patterns of climate. The North Atlantic oscillation (NAO) is a large-scale climate phenomenon that has been shown to influence the population dynamics of some animals. Although effects of the NAO on vertebrate population dynamics have been studied, it remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…Morrison and Hik (2007) found a positive effect of Pacific Decadal Oscillation (PDO) on collared pika (Ochotona collaris) adult survival, likely due to its effects on timing of spring snowmelt which occurred later during years with low PDO. In contrast to the pika study, Wang et al (2002b) found that local climate had a bigger influence on white-tailed ptarmigan population dynamics at RMNP than large-scale climate measures. No relationships between NAO and local climate patterns relevant to white-tailed ptarmigan demographics have been identified, and we did not find strong correlations between winter weather covariates tested and winter NAO.…”
Section: Population Recruitmentcontrasting
confidence: 96%
“…Morrison and Hik (2007) found a positive effect of Pacific Decadal Oscillation (PDO) on collared pika (Ochotona collaris) adult survival, likely due to its effects on timing of spring snowmelt which occurred later during years with low PDO. In contrast to the pika study, Wang et al (2002b) found that local climate had a bigger influence on white-tailed ptarmigan population dynamics at RMNP than large-scale climate measures. No relationships between NAO and local climate patterns relevant to white-tailed ptarmigan demographics have been identified, and we did not find strong correlations between winter weather covariates tested and winter NAO.…”
Section: Population Recruitmentcontrasting
confidence: 96%
“…In one study by Wang et al . (), local minimum winter temperatures had a stronger effect on White‐tailed Ptarmigan population dynamics than large‐scale indices like NAO. On the other hand, Wann et al .…”
Section: Resultsmentioning
confidence: 88%
“…the North Atlantic Oscillation (NAO) index. In a study of the white-tailed ptarmigan, Wang et al (2002b) reported that the local climate had a stronger signature on the demography of the species than did a largescale climate index. The use of the NAO index, as in the study by Barnagaud et al (2011) investigating the effect of climate on the breeding success of black grouse Lyrurus tetrix in the French Alps, would likely have been more appropriate if Rock Ptarmigan breeding success had been recorded over a broader scale.…”
Section: Discussionmentioning
confidence: 98%